In vitro Efficacy Comparisons of Disinfectants Used in the Commercial Poultry Farms - Gehan, Z. Moustafa; Anwer, W.; Amer, H.M.; EL-Sabagh, I.M.; Rezk, A.; Badawy, E.M. (International Journal of Poultry Science, 2009)
Studies have indicated variations in the degree of efficacy of the commercial disinfectants commonly used in poultry production facilities. An adequate method of in vitro testing was used to compare the efficacy of some of these disinfectants while testing them in conditions similar to those of the poultry facilities. Five commercially available disinfectants were tested against 7 selected bacterial, fungal and viral isolates. The obtained results indicated that, most of the tested disinfectant products were effective at the manufacturer recommended level within 30 min contact time when tested in the absence of organic matter. However, when organic matter was present longer contact times were needed to demonstrate the effectiveness. Pseudomonas aeruginosa, Fusarium species and Newcastle disease virus showed variable degrees of resistance to some of the tested disinfectant products in the presence of organic matter. Conclusively, monitoring program should be adopted regularly in poultry facilities to test the problematic microbes individually for their resistance against commercial disinfectants.